The ratification of the 1951 refugees convention: protection of the rights of asylum seekers in Malaysia / Amsyar Ahmad Zawawi, Maziah Martin and Mohammad Afif Daud - Ahmad Zawawi, Amsyar; Martin, Maziah; Daud, Mohammad Afif (Faculty of Law, 2012)
This project paper discusses the issue of ratification of the 1951 Convention relating to the Status of Refugees (also known as the 1951 Refugees Convention) in order to provide protections and rights to asylum seekers in Malaysia. The project paper outlines our research proposal which consists of basic layouts in conducting our research. It comprises of the historical development of the law on asylum seekers throughout the years, basically before and after the introduction of the 1951 Refugees Convention. Furthermore, this project paper illustrates the present situation in regards to the protection of asylum seekers in Malaysia as Malaysia currently is not a party to the said convention. Subsequently, we will look into practices by countries that had ratified the 1951 Refugees Convention, more specifically United Kingdom and Australia; to know the basic standard of care and the treatment provided by these countries in the protection of asylum seekers. Conjointly, this project paper explores on the issue of conflict on duties of states on asylum seekers, as well as the settlement on the issue of rights of asylum seekers. In addition to all the foregoing, this project paper highlights on recommendations to be observed to protect the rights of asylum seekers.